MANAJEMEN PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN JASMANI SEKOLAH MENENGAH ATAS (SMA) NEGERI DI KOTA YOGYAKARTA - Rohmansyah, Nur Azis (Journal of Sport Science and Education, 2018)
The purpose of this study is to describe the professionalism condition of high school teachers (SMA) in the city of Yogyakarta. The method used in this research used qualitative research method with case study type with observation data taking technique, interview, and document study. The study was conducted in Yogyakarta City by taking data in several senior high schools in Yogyakarta consisting of the headmaster, the head of MGMP Yogyakarta, and the sport education teacher who had met the criteria on the selection of informants. Data analysis technique using QSR NVivo Plus 11. The result of research of professionalism condition of sport education teacher in Yogyakarta city can not be said high, this is because there are still many problems that influence the level of professionalism of sport education teacher in Yogyakarta City, such as facilities and infrastructure which not yet adequate, Teaching that still uses conventional methods, and administrative flaws. Based on the above conclusions, the results of this study have implications of High School Teachers in all cities of Yogyakarta to further improve their competence through various ways to be more competent to be physical education teachers so as to channel knowledge useful and good for learners.